Neurocysticercosis Presented with Acute Psychosis: A Case Report - Thapa, Dinesh K; Limbu, Chandra P; Gurung, Ajit; Pant, Basant (Nepal Journal of Neuroscience, 2016)
Neurocysticercosis is the parasitic disease caused by ingestion of egg of Tinae Solium. The disease presents with spectrum of clinical manifestations like seizure, headache, neurological deficit and psychiatric symptoms such as psychosis. Even though most commonly patients of neurocysticercosis present with seizure, rarely, it may produce symptoms of neuropsychiatric disorder such as psychosis. Here, we are going to report a case of a patient who presented with features of acute psychosis. Later on with diagnostic imaging like CT and MRI, he was diagnosed as a case of multiple neurocysticercosis. He was then managed with anti psychotics, AEDs, Anti-helminthic drugs and steroids. Nepal Journal of Neuroscience 13:54-56, 2016